2022
DOI: 10.1089/apc.2022.0020
|View full text |Cite
|
Sign up to set email alerts
|

Roles, Barriers, and Recommendations for Community Health Workers Providing Community-Based HIV Care in Sub-Saharan Africa: A Review

Abstract: While the impact of Community Health Workers (CHWs) on home-based human immunodeficiency virus (HIV) care has been documented, barriers and recommendations have not been systematically reviewed. Following the reporting requirements of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, we used an aggregative narrative synthesis approach to summarize the results of qualitative studies published between January 1, 2000, and November 6, 2020 in the following databases: PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 66 publications
(173 reference statements)
0
12
0
Order By: Relevance
“…In resource limited countries, there is greater availability of CHWs for HIV care, and research is being directed to developing, testing, and establishing community based models for support of adherence and retention in care [ 86 ]. However, recommendations to optimize the CHW role for HIV support in LMICs calls for improved training and supervision, better care coordination, integration of patient centered mHealth approaches, and increased funding [ 87 , 88 ]. In the US, the CHW role in HIV care and research continues to evolve, and best practices for training, retaining and integrating CHWs into clinical and research teams remain to be determined.…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
“…In resource limited countries, there is greater availability of CHWs for HIV care, and research is being directed to developing, testing, and establishing community based models for support of adherence and retention in care [ 86 ]. However, recommendations to optimize the CHW role for HIV support in LMICs calls for improved training and supervision, better care coordination, integration of patient centered mHealth approaches, and increased funding [ 87 , 88 ]. In the US, the CHW role in HIV care and research continues to evolve, and best practices for training, retaining and integrating CHWs into clinical and research teams remain to be determined.…”
Section: Conclusion and Next Stepsmentioning
confidence: 99%
“…Twelve (12) participants were purposively recruited into the study. All the participants were married aged between 32 and 68 years.…”
Section: Demographic Characteristics Of the Participantsmentioning
confidence: 99%
“…In other studies, it was reported that many different barriers to community-based HIV care were reported and they were stigma and nondisclosure; inadequate support (lack of resources, inadequate training, inadequate funding, and inadequate monitoring). 12,28 This greatly hindered the work of the expert clients. Significant efforts should be made to mitigate these barriers by addressing HIV-…”
Section: Experiences Of Expert Clients In Reducing Stigma and Discrim...mentioning
confidence: 99%
See 2 more Smart Citations